Caracterização do desempenho em plataforma de força de atletas pós lesão de ligamento cruzado anterior: um estudo transversal - Carvalho, Sergio Luis Falci de (2020)
The aim of the present study was to characterize and compare the performance of lower limbs of athletes with anterior cruciate ligament injury (ACL) as an indicator of return to sports practice. The decision to release after an anterior cruciate ligament injury must be shared between the health team responsible for monitoring recovery, coaches, and the athlete. Assessments throughout the recovery provide support for decisions to be made more assertively. In this sense, this study used a force plate to measure lower limb performance in high-performance athletes through jumping and balance testing. For this observational study, the sample of 17 high performance athletes (volleyball, basketball, judo, artistic gymnastics and trampoline) was in the process of recovering from ACL injuries, 8 of whom were female and 9 were male, with an average of age of 20±0.5 years. The countermovement and balance jump assessment were performed in a bipodal and unipodal manner. In this work, the Mann-Whitney non-parametric test was chosen to identify differences in results with two legs and only one and the Wilcoxon to identify differences between injured and uninjured limbs. To identify improvements in performance measures throughout the recovery process, the Kruskal- Wallis non-parametric test is used, in addition to analyzing Spearman's correlations with time numerically. In the countermovement, the main performance variable (heel height) showed a significant difference (p = 0.03), as well as in the force development rate (RFD), which presented p = 0.04. For balance measures, none of the comparisons was significant. Therefore, it can be concluded that the balance results are independent of the leg used being the injured one. The expected performance is different when compared between the injured and the uninjured limb, being an indicator for developing intervention strategies to reduce asymmetries and recover the performance prior to the injury, as well as guaranteeing a safe return to training and games. However, the results obtained must be analyzed individually, considering the evolution of the treatment. It was not possible to establish common characteristics in the athletes' performance in different stages of recovery, despite differences between injured and uninjured limbs being present.